Clinical and myopathological evaluation of early- and late-onset subtypes of myofibrillar myopathy - Olivé, Montse; Odgerel, Zagaa; Martínez, Amaia; Poza, Juan José; Bragado, Federico García; Zabalza, Ramón J.; Jericó, Ivonne; Gonzalez-Mera, Laura; Shatunov, Alexey; Lee, Hee Suk; Armstrong, Judith; Maraví, Elías; et al. (Neuromuscular disorders : NMD, 2011)
Myofibrillar myopathies (MFM) are a group of disorders associated with mutations in DES, CRYAB, MYOT, ZASP, FLNC, or BAG3 genes and characterized by disintegration of myofibrils and accumulation of degradation products into intracellular inclusions. We retrospectively evaluated 53 MFM patients from 35 Spanish families. Studies included neurologic exam, muscle imaging, light and electron microscopic analysis of muscle biopsy, respiratory function testing and cardiologic work-up. Search for pathogenic mutations was accomplished by sequencing of coding regions of the six genes known to cause MFM. Mutations in MYOT were the predominant cause of MFM in Spain affecting 18 of 35 families, followed by DES in 11 and ZASP in 3; in 3 families the cause of MFM remains undetermined. Comparative analysis of DES, MYOT and ZASP associated phenotypes demonstrates substantial phenotypic distinctions that should be considered in studies of disease pathogenesis, for optimization of subtype-specific treatments and management, and directing molecular analysis.